Internationalisation and the innovation activities of services firms - Iulia Siedschlag; Neill Killeen; Donal Smith; Catriona O'Brien (The Economic and Social Research Institute (ESRI), 2011)
This paper examines the relationship between the internationalisation of firms in services and their innovation performance. We use firm-level data over the period 2004-2006 and estimate an augmented structural model to account for the role of foreign direct investment and exporting on the innovation performance of services firms in Ireland. Our research shows that in comparison to firms serving only the Irish market, domestic exporters were more likely to engage in R&D and innovation and they were more likely to be successful in terms of innovation output, over and above firm characteristics such as size and distance to the technology frontier. Further, we find that adoption of information and communication technologies was positively associated with innovation output. Co-operation with suppliers was positively associated with all innovation types, while knowledge flows from customers and from the government or public research institutes were positively linked to product innovation. Co-operation with universities was positively linked to innovation measured by patents.
Keywords: 330; Multinational Firms; Exporting; Knowledge Production; Services; Unternehmenspolitik; Unternehmensdienstleistung; Multinationales Unternehmen; Auslandsinvestition; Industrieforschung; Innovationsmanagement; Irland